Establishing a novel inflammatory bowel disease prediction model based on gene markers identified from single nucleotide variants of the intestinal microbiota. Issue 3 (24th July 2022) - Jiang, Shuaiming; Chen, Denghui; Ma, Chenchen; Liu, Huanwei; Huang, Shi; Zhang, Jiachao
Abstract: The intestinal microbiota is a crucial environmental factor in the development of inflammatory bowel disease (IBD). The abundance of Faecalibacterium prausnitzii is significantly decreased in IBD patients, which is used as a biomarker for IBD diagnosis. However, this can be observed in both IBD and colorectal cancer, which would confound the diagnostic results. Thus, we first established a new model for predicting Crohn's disease (CD) with high precision according to gene characteristics based on single nucleotide variants (SNVs). Next, five gene markers belonging to two species, F. prausnitzii and Eubacterium rectale, that were enriched in the CD group were obtained to build a CD prediction model, and high accuracy in distinguishing the CD and control groups was observed in the discovery (area under curve [AUC] = 91.13%) and validation cohorts (AUC = 79.55%). The model still maintained high accuracy after expanding the healthy cohort (AUC = 89.75%). High disease specificity in distinguishing CD and CRC groups (AUC = 95.74%) was also proven. This study establishes a novel diagnostic method for predicting IBD that also provides unprecedented insight for the early, painless diagnosis of other non‐communicable diseases. Abstract : Specific gene characteristics based on single nucleotide variants were identified in intestinal microbiota genes of inflammatory bowel disease (IBD) patients. A novel and accurate diagnostic method for predicting IBD was established. Faecalibacterium prausnitzii showed a decreased abundance in different diseases and carried disease‐specific mutation sites within genes. Highlights: Specific gene characteristics based on single nucleotide variants were identified in intestinal microbiome of inflammatory bowel disease (IBD) patients. A novel and accurate diagnostic method for predicting IBD was established. Faecalibacterium prausnitzii showed a decreased abundance in different diseases and carried disease‐specific mutation sites within genes.